Standardizing Support Surface Testing and Reporting: A National Pressure Ulcer Advisory Panel Executive Summary. Issue 5 (September 2015) - Stone, Arthur; Brienza, David; Call, Evan; Fontaine, Rick; Goldberg, Margaret; Hong, K. Z.; Jordan, Rosalyn; Lachenbruch, Charlie; LaFleche, Patrick; Sylvia, Cindy
Abstract : In 2001, the National Pressure Ulcer Advisory Panel's Research Committee identified the need to create uniform terminology, test methods, and reporting technical standards for support surfaces. As a result, the S3I Committee was formed and initial meetings of interested stakeholders who included clinicians, researchers, academics, manufacturers, providers, and regulators were held. The group's initial goal was to (1) establish common language to facilitate understanding by developing standardized terminology for describing and discussing support surfaces, (2) establish a suite of standardized tests of performance capable of repeatedly, reliably, and accurately reporting upon characteristics common to all support surfaces that are believed to be related to the extrinsic risk factors associated with skin breakdown, as indicated by the literature to date, and (3) identify and standardize methods to evaluate the effective life of a support surface. The purpose of this article was to summarize the current status of the effort of the Support Surface Standards Initiative (S3I) Committee to identify and standardize methods to evaluate the many characteristic factors that determine the effective life of a support surface.